Efficacy and tolerance of enteral nutrition in children with biliary atresia awaiting liver transplantation - Privat, Elodie; Aumar, Madeleine; Ley, Delphine; Tran, Léa Chantal; Coopman, Stéphanie; Guimber, Dominique; Turck, Dominique; Gottrand, Frédéric (Frontiers in Pediatrics, 2022)
Objectives: Malnutrition is common in children with biliary atresia (BA) awaiting liver transplantation (LT). Few studies have evaluated the effectiveness of enteral nutrition (EN) in these patients. The objective of this work was to assess the efficacy and tolerance of EN in children with BA waiting for LT. Methods: A total of 31 patients with BA followed between 1995 and 2018 were retrospectively included. Anthropometric indicators (weight, length, head circumference) and adverse effects of EN were noted at the start (T0) and the end (T1) of EN. The z scores for anthropometric indicators were compared between T0 and T1. Results: The median age at T0 was 7 months (interquartile range (IQR), 5–9) and median duration of EN was 9 months (IQR, 3–17). The z scores for anthropometric variables improved from T0 to T1: –1.6 (IQR, –2.5 to –1.0) to –0.5 (IQR, –1.8 to 0.3) for median weight for age; –1.3 (IQR, –2.4 to 0) to –0.4 (IQR –2.0 to 0.7) for length for age; –0.9 (IQR, –2.3 to –0.3) to –0.3 (IQR, –1.2 to 0.1) for weight for length; and –1.2 (IQR –2.1 to –0.6) to –0.2 (IQR, –1.6 to 0.4) for body mass index (P < 0.05 for all comparisons). Nearly all (94%) of patients had a weight-for-length z score >–2 at the end of EN; 23% had minor adverse effects and 10% had complications leading to cessation of EN. Conclusions: EN is effective and well tolerated in infants with BA waiting for LT.